Protein Kinases: Potential Drug Targets Against Schistosoma japonicum - Wu, Kaijuan; Zhai, Xingyu; Huang, Shuaiqin; Jiang, Liping; Yu, Zheng; Huang, Jing (Frontiers in Cellular and Infection Microbiology, 2021)
Schistosoma japonicum (S. japonicum) infection can induce serious organ damage and cause schistosomiasis japonica which is mainly prevalent in Asia and currently one of the most seriously neglected tropical diseases. Treatment of schistosomiasis largely depends on the drug praziquantel (PZQ), however, PZQ exhibits low killing efficacy on juvenile worms and the potential emergence of its drug resistance is a continual concern. Protein kinases (PKs) are enzymes that catalyze the phosphorylation of proteins and can participate in many signaling pathways in vivo. Recent studies confirmed the essential roles of PKs in the growth and development of S. japonicum, as well as in schistosome-host interactions, and several researches have screened some drug targets mainly including PKs from S. japonicum (SjPKs), which provide new opportunities of developing new treatments on schistosomiasis. The aim of this review is to present the current progress on the important roles of various SjPKs from different perspectives and their potentials to become drug targets compared with other schistosomes. The efficiency of related protein kinase inhibitors on schistosomes is highlighted. Finally, the current challenges and problems in the study of SjPKs are proposed, which can provide future guidance for developing anti-schistosomiasis drugs and vaccines.